Título Padrão: evolução e paradigmas da ciência - Reis, Makson de Jesus; Carvalho, Telma de (Informação em Pauta, 2022)
The evolution of Science makes it possible to go through the understanding of the evolutionary process of society, being based on scientific paradigms and research. Knowledge in the scientific field has its definition based on the density of the empirical base, being built by its paradigms. In this foundation, through the process of technological development, which four paradigms make up science, being first for the description of natural phenomena, the second for the use of models, third for the computational branch, in the simulations of these phenomena and the fourth for the great amount of data, which through this advance, this great sharing of data and its storage, propitiate the emergence of e-science, formed by the flood of data, which are collected, generated or simulated by computing. The article aims to discuss the relationship between data science and information science. Using as methodological study the use of literature review. Thus, it is concluded, that seeking to understand the paradigms of e-science are essential to study the behavior of the current era of the large amount of data emerging from the web.